Incubation time in the stress corrosion cracking of a low carbon steel, a fracture mechanics approach using the J integral parameter - Koru, Adnan S. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1983., 1983)
The inoubation period assooiated with the advanoe of a stress oorrosion crack in a low carbon steel exposed to sulphuric acid is investigated. Fatigue pre-cracked Cantilever Beam Specimens are tested in accordance with Fracture Mechanics methodology. Regarding the fact that the application of the Linear-Elastic-Stress-Intensity-Factor K to stress corrosion problems has met with extended success, the J Integral parameter with its broader scope of applioation is used in the same context. Considerable emphasis is plaoed upon establishing an effective and straightforward experimental method. Results obtained olearly indicate-that the J Integral parameter is suitable forpredioting inoubation behaviour.
Keywords: Stress corrosion.; Metals -- Fatigue.; Metals -- Stress corrosion.; Fracture mechanics.